How a teacher professional development program influences students' algebra performance? Reflections from a web-based platform - Dilek Tanışlı; Handegül Türkmen; Melih Turgut; Nilüfer Köse (Journal of Pedagogical Research, 2020)
The main purpose of this study was to assess seventh-graders' algebra performance when their teachers received professional development support regarding hypothetical learning trajectories through a web-based platform. Secondly, we aimed to investigate the relationship between student performance and the teachers' professional development in teaching algebra. A mixed-method research paradigm was adopted into the study. Experimental research was conducted with nine experimental and nine control groups including 454 seven graders. The data came from a combined algebra (including open-ended and multiple-choice tasks) test and experimental group teachers' teaching designs where the plans were entered to the web-based platform. Statistical methods were used to analyse the quantitative data, while descriptive methods were used to analyse the qualitative data. The results revealed that the experimental-group students (whose teachers received professional development support through the web-based platform) statistically outperformed compared to those in control groups. Besides, a relationship between was found between the experimental group teachers' progress and algebra performance of their students.